Cybersecurity Threat Analysis and Risk Assessment for Intelligent Connected Vehicles - XIE, Huasheng; WANG, Lie (Promet - Traffic&Transportation, 2026)
With the rapid development of intelligent connected vehicles, cybersecurity issues have become increasingly prominent, posing significant challenges to vehicle safety and user privacy. This paper conducts a study on threat analysis and risk assessment (TARA) for intelligent connected vehicles based on the ISO/SAE 21434 standard. The research analyses and examines the practical methodologies of the standard from systematic and practical perspectives, constructing a comprehensive risk assessment framework that covers risk identification, analysis, assessment and response strategies. The rationality and effectiveness of the framework are validated through case studies. This study not only provides systematic security guidance for automotive manufacturers and technology developers but also offers empirical evidence for regulatory compliance reviews, thereby promoting the secure development of intelligent connected vehicles.